An alternative to hydrogenation processes. Electrocatalytic hydrogenation of benzophenone - Mozo Mulero, Cristina; Sáez, Alfonso; Iniesta, Jesús; Montiel, Vicente (Beilstein Journal of Organic Chemistry, 2018)
The electrocatalytic hydrogenation of benzophenone was performed at room temperature and atmospheric pressure using a polymer electrolyte membrane electrochemical reactor (PEMER). Palladium (Pd) nanoparticles were synthesised and supported on a carbonaceous matrix (Pd/C) with a 28 wt % of Pd with respect to carbon material. Pd/C was characterised by transmission electron microscopy (TEM), and thermogravimetric analysis (TGA). Cathodes were prepared using Pd electrocatalytic loadings (LPd) of 0.2 and 0.02 mg cm−2. The anode consisted of hydrogen gas diffusion for the electrooxidation of hydrogen gas, and a 117 Nafion exchange membrane acted as a cationic polymer electrolyte membrane. Benzophenone solution was electrochemically hydrogenated in EtOH/water (90/10 v/v) plus 0.1 M H2SO4. Current densities of 10, 15 and 20 mA cm−2 were analysed for the preparative electrochemical hydrogenation of benzophenone and such results led to the highest fractional conversion (XR) of around 30% and a selectivity over 90% for the synthesis of diphenylmethanol upon the lowest current density. With regards to an increase by ten times the Pd electrocatalytic loading the electrocatalytic hydrogenation led neither to an increase in fractional conversion nor to a change in selectivity.
Keywords: benzophenone; diphenylmethanol; electrocatalytic hydrogenation; palladium nanoparticles; polymer electrolyte membrane